EDUCATIONAL STANDARDS IN DAILY PLANS OF THE SERBIAN LANGUAGE COURSE - Татјана М. Вјештица (Metodički Vidici, 2012)
This article first lists the basic explanations on educational standards and their characteristics, with a special review of the educational standards for the Serbian language. Then it gives suggestions for using these educational standards in real teaching units in different areas and at different levels of students’ accomplishments.